Parenting and teaching young children - Hildebrand, Verna (New York Webster Division, McGraw-Hill, 1981)
A home economics textbook that discusses aspects of child development including parenthood, child care, and day care facilities.
Includes bibliographies and index.
Keywords: Parenting; Child care; Child development; Child development; Parenting